Lifelong cerebrovascular disease burden among CADASIL patients: analysis from a global health research network - Pan, Alan P.; Potter, Thomas; Bako, Abdulaziz; Tannous, Jonika; Seshadri, Sudha; McCullough, Louise D.; Vahidy, Farhaan S. (Frontiers in Neurology, 2023)
Introduction Data reporting on patients with Cerebral Autosomal Dominant Arteriopathy with Subcortical Infarcts and Leukoencephalopathy (CADASIL) within the United States population is limited. We sought to evaluate the overt cerebrovascular disease burden among patients with CADASIL. Methods Harmonized electronic medical records were extracted from the TriNetX global health research network. CADASIL patients were identified using diagnostic codes and those with/without history of documented stroke sub-types (ischemic stroke [IS], intracerebral hemorrhage [ICH], subarachnoid hemorrhage [SAH] and transient ischemic attack [TIA]) were compared. Adjusted odds ratios (OR) and 95% confidence intervals (CI) of stroke incidence and mortality associated with sex were computed. Results Between September 2018 and April 2020, 914 CADASIL patients were identified (median [IQR] age: 60 [50–69], 61.3% females); of whom 596 (65.2%) had documented cerebrovascular events (i.e., CADASIL-Stroke patients). Among CADASIL-Stroke patients, 89.4% experienced an IS, co-existing with TIAs in 27.7% and hemorrhagic strokes in 6.2%; initial stroke events occurred ≤65 years of age in 71% of patients. CADASIL-Stroke patients (vs. CADASIL-non-Stroke) had higher cardiovascular and neurological (migraines, cognitive impairment, epilepsy/seizures, mood disorders) burden. In age- and comorbidity-adjusted models, males had higher associated risk of stroke onset (OR: 1.37, CI: 1.01–1.86). Mortality risk was higher for males (OR: 2.72, CI: 1.53–4.84). Discussion Early screening and targeted treatment strategies are warranted to help CADASIL patients with symptom management and risk mitigation.